Treatment of Leishmania (Leishmania) Amazonensis-Infected Mice with a Combination of a Palladacycle Complex and Heat-Killed Propionibacterium acnes Triggers Protective Cellular Immune Responses - Paladi, Carolina S.; da Silva, Danielle A. M.; Motta, Priscila D.; Garcia, Daniel M.; Teixeira, Daniela; Longo-Maugéri, Ieda M.; Katz, Simone; Barbiéri, Clara L. (Frontiers in Microbiology, 2017)
Palladacycle complex DPPE 1.2 was previously reported to inhibit the in vitro and in vivo infection by Leishmania (Leishmania) amazonensis. The aim of the present study was to compare the effect of DPPE 1.2, in association with heat-killed Propionibacterium acnes, on L. (L.) amazonensis infection in two mouse strains, BALB/c and C57BL/6, and to evaluate the immune responses of the treated animals. Foot lesions of L. (L.) amazonensis-infected mice were injected with DPPE 1.2 alone, or associated with P. acnes as an adjuvant. Analysis of T-cell populations in the treated mice and in untreated controls was performed by FACS. Detection of IFN-γ-secreting lymphocytes was carried out by an ELISPOT assay and active TGF-β was measured by means of a double-sandwich ELISA test. The treatment with DPPE 1.2 resulted in a significant reduction of foot lesion sizes and parasite burdens in both mouse strains, and the lowest parasite burden was found in mice treated with DPPE 1.2 plus P. acnes. Mice treated with DPPE 1.2 alone displayed a significant increase of TCD4+ and TCD8+ lymphocytes and IFN-γ secretion which were significantly higher in animals treated with DPPE 1.2 plus P. acnes. A significant reduction of active TGF-β was observed in mice treated with DPPE 1.2 alone or associated with P. acnes. Moreover, DPPE 1.2 associated to P. acnes was nontoxic to treated animals. The destruction of L. (L.) amazonensis by DPPE 1.2 was followed by host inflammatory responses which were exacerbated when the pallladacycle complex was associated with P. acnes.